Unveiling the Determinants of Farmer Motivation in Goat Production: Evidence from Goat Farmers in Jombang District, East Java, Indonesia - Nugroho, Eko; Sugeng Winarto, Priyo; Ibnu Khafid, Syaiful (ANIMAL PRODUCTION, 2025)
Goat farming is an essential livelihood strategy for rural communities, providing substantial economic and social advantages. However, there remains a vague understanding of the underlying motivations driving smallholder goat farmers' engagement, particularly in contexts with diverse socio-demographics and resource limitations. This study aimed to determine the most influential factors in goat-farming decisions by conducting a cross-sectional survey of 50 smallholder goat farmers. Data collection encompassed socio-demographic variables, as well as access to capital, infrastructure, market conditions, and policy support. Results revealed that capital and infrastructure significantly outweighed age, education, and farming experience in shaping farmers’ level of involvement. Local markets received favorable ratings, but inconsistent government support highlighted significant policy gaps. Larger households benefited from greater labor availability, yet did not consistently adopt best practices. These findings highlight the primacy of resource-based and socio-familial factors in shaping smallholder motivation and illustrate the need for targeted interventions. Enhanced collaboration among government agencies, cooperatives, and community groups may promote more resilient and profitable goat-farming systems.